Изобразительное искусство: [энциклопедия] / [ред. О. Медведская] - Медведская О. (Большая серия знаний, 2006)
Экземпляры: ф. 6 (20151027) / Инвентарный номер: 60459 / Цена: 100.00 / Авт.знак: И 38 / ГРНТИ: 18 / ББК: 85.14я2